Load Control for Energy Optimalization in Unstabil Electric Power Plant - Iswanjono, Iswanjono (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The power generated by a power plant driven by windmills and waterwheels and solar power is unstable,. each depends on wind speed, water flow, and solar radiation, repeatively. This results in the acquisition of energy not being optimal if the load is not adjusted to the capability of the generating power. In this study a load control automation system has been created that can adjust to the ability of the resource so that optimal energy is obtained by the hysteresis method. When the power goes up and down the load adjusts hysterically, so that optimal energy is obtained.